Wybrane nowoczesne formy i narzędzia zarządzania marketingowego - Binsztok, Aleksander (Chosen modern forms and tools of the marketing management, 2005)
In this article an author underlines the need of using the modem forms and tools of the marketing anagement. Basing on their main attitudes of the described subjects, author presents: global marketing, how to create corporate identity and the value for the clients, lobbying in the Internet network, hidden marketing, CRM (Customer Relationship Management), Contact Centre and the CEM (Customer Experience Management). On the end of this article an author has described the attitudes of the marketing manager.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 217-226